Framework for systematic design, analysis and evaluation of intrusion detection systems - Li, Zhuowei (2008)
Intrusion detection has become a critical component of the security infrastructure in the face of increasing vulnerabilities and threats in Internet applications. However, most intrusion detection techniques are stymied by a number of fundamental and practical problems, such as intrusion variation detection, higher false alarm rate. In this thesis, we will refer to these problems as the generic problems of intrusion detection, and propose a systematic approach to identify the root cause of these problems, analyze them and devise several solution to address them.